Estrutura da comunidade de borboletas (Lepidoptera: Papilionoidea) na Amazônia Oriental Maranhense, Brasil - Carvalho, Rosilda Rodrigues de (2021)
The order Lepidoptera is composed of butterflies and moths, which play an important role in ecological processes. This group of insects has been widely used in monitoring of natural environments for presenting characteristics that facilitate sampling and identification. Fragmentation and habitat destruction are among the main threats to these organisms, and the implementation of Conservation Units (UCs) is one of the strategies to protect biodiversity. This study aimed to compare the structure of frugivorous butterfly communities in three UCs: Itapiracó Environmental Protection Area (Itapiracó APA); Maracanã Environmental Protection Area (APA do Maracanã) and the Sitio do Rangedor State Park (Sítio do Rangedor), and in the Reserve owned by the Quercegen Agronegócios Company (Sítio Aguahy), and to prepare an illustrated guide to lepidopteran species. Collections were carried out between September 2019 and January 2021. Sampling followed the standardized methodology for frugivorous butterflies using Van Someren-Rydon traps. Thirty traps were used, which remained in the field for five consecutive days, being inspected every 24 hours to collect the butterflies and replace the baits. Easy-to-identify specimens were numerically marked, photographed and released. Individuals of uncertain identification and witness specimens were collected, identified and deposited in the Entomological Collection “Iraci Paiva Coelho” (CIPC) of the State University of Maranhão. A record of 2,868 individuals was obtained, 1,229 for the APA of Itapiracó, 919 for the APA of Maracanã, 379 individuals for the Sítio do Rangedor and 341 for the Sítio Aguahy. Of the 52 species recorded in this study, Taygetis laches and Opsiphanes invirae were the two most abundant with 570 and 382 individuals, respectively. Species richness, abundance, evenness and dominance were analyzed using the following estimators: Simpson1-D; Shannon-H; Equitability-J and Berger- Parker. Differences in species composition were found between the sampled areas. The Aguahy Site showed greater diversity (H'=3.13), less dominance (D'= 0.94), greater evenness (J'=0.89) and greater species richness. The Rangedor Site showed lower diversity, higher dominance and lower evenness (H'=2.10; D'=0.79; J'=0.67), respectively. For the APA of Itapiracó and APA of Maracanã, higher abundances were recorded. The data obtained indicate that there are differences in the composition of the communities of frugivorous butterflies in the study areas with different degrees of disturbance. The Butterfly Guide was composed of 25 colored boards with digital images of frugivorous and nectarivorous butterflies sampled in the Eastern Amazon of Maranhense. The species were presented on the dorsal (D) and ventral (V) face, with distinction of male (♂) and female (♀), in case of sexual dimorphism.